Actor Collaboration in Overcoming Road Damage in Karawang District - Idris, Norhalimas (Decision, 2022)
To improve one's position, development is a process of ongoing renewal. Many developing countries invest in development projects to reinvigorate their economies. Assuming that every citizen has the opportunity to participate, the government's proactive role and purposeful attempts to improve many parts of a country's political, economic, and sociocultural life may be successful. This study took a normative research approach, adhering to recognized norms for qualitative analysis. It is based on secondary data gathered from numerous sources, including primary, secondary, and tertiary sources of legal information. Through the use of sources, documentation, observation, and other methods of data collection. To address damage to road infrastructure in other regions of Karawang Regency, this study will look at the role of local governments in repairing these sections. However, because to financial constraints and inconvenient building sites, the Karawang Regency local government was unable to repair the damaged road infrastructure.